2015
DOI: 10.3103/s0096392515040070
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of 8-oxo-2'-deoxyguanosine

Abstract: The review presents currently available data on the biological role of 8-oxo-2'-deoxyguanosine. This compound has been successfully and for a long time used as a biomarker of oxidative stress and diseases associated with it. However, in recent years an increasing number of publications has appeared reporting that 8-oxo-dG is not simply a byproduct of oxidation processes, but is of great biological importance. It is assumed that it is involved in the regulation of gene expression, in some processes of DNA repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…It may be the result of ROS synthesis induction in that cells, or possibly, the oxidized DNA accumulates in them. First, it is believed that the oxidative deoxyguanosine modifications in DNA are exclusively genotoxic and mutagenic and, therefore, harm nucleic acids [50, 51]; second, it is assumed that easily oxidized G in the cfDNA composition may act as the intracellular antioxidant [41].…”
Section: Discussionmentioning
confidence: 99%
“…It may be the result of ROS synthesis induction in that cells, or possibly, the oxidized DNA accumulates in them. First, it is believed that the oxidative deoxyguanosine modifications in DNA are exclusively genotoxic and mutagenic and, therefore, harm nucleic acids [50, 51]; second, it is assumed that easily oxidized G in the cfDNA composition may act as the intracellular antioxidant [41].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in genetic information, mutagenesis, and cellular apoptosis associated with this make oxidative damage of nucleic acids one of the most dangerous modifications among biomolecules [5]. It was previously shown that of the four bases, which make up the DNA structure, guanine is the most oxidized [6]. Among the most important biological OS markers there are the following purines: 8-hydroxy-2'-deoxyguanosine (8-OHdG) or its oxidized form 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important biological OS markers there are the following purines: 8-hydroxy-2'-deoxyguanosine (8-OHdG) or its oxidized form 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG). 8-OHdG is considered as the most sensitive and useful marker of oxidative DNA damage [7,8], which can be found in many tissues and fluids as it easily penetrates from cells into the blood [6]. However, the biological role of 8-OHdG is currently poorly understood [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…В последнее десятилетие появились исследования, сообщающие о вероятной значимой биологической роли 8-oxo-dG [5] и открывающие перспективы применения его в качестве лекарственного препарата. В частности, были показаны выраженные противовоспалительный [6] и иммунорегулирующий [7] эффекты этого соединения, а также выдвинута гипотеза о его важной роли в регуляции репарации ДНК и ее сопряжении с внутриклеточной сигнализацией [8].…”
Section: Introductionunclassified